Substance use disorders: Need for public health initiatives - Rakesh Kumar Chadda (Indian Journal of Social Psychiatry, 2019)
Substance use disorders (SUDs) are associated with substantial contribution to the global burden of disease due to high prevalence, early age of onset, and chronic course. The associated physical health complications such as HIV, hepatitis B and C, and opportunist infections, stigma, myths and misconceptions, and a huge treatment gap further increase the problem. Thus, there is a strong need to take public health initiatives. Conventionally, common substances of abuse include licit substances such as tobacco and alcohol and illicit substances such as opioids, cannabis products, cocaine, barbiturates, amphetamines, and prescription drugs. The new psychoactive substances have brought a new challenge. Conventionally, the three approaches of supply reduction, demand reduction and harm reduction have been used to deal with the problem of SUDs. Preventive strategies encompassing primary, secondary, and tertiary methods need to be formally planned to meet this massive challenge. Creating awareness about the problem in the community and targeting myths and misconceptions are important to reduce the treatment gap. There is need to ensure availability and accessibility of affordable and acceptable treatment facilities, provide evidence-based treatment, and ensure ethical standards in care including coordination between health, social, and legal agencies. Relapse prevention and rehabilitation also need to be an important component of the public health policy. A well-planned public health approach involving all stakeholders is likely to be the most appropriate method to deal with the challenges imposed by the SUDs.